Langkah Penyelesaian Perselisihan Pemutusan Hubungan Kerja (Phk) Sepihak Serta Upaya Perlindungan Pekerja Studi Kasus Pt. Kaldu Sari Nabati Indonesia - Delia Nurul Nuraeni; Muhamad Rizal; Sari Usih Natari (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The purpose of this research is to find out the process of resolving disputes over Termination of Employment (PHK) pursued by trade unions based on Law number 2 of 2004 and Law of Job Creation and knowing the protection efforts for workers who were unilaterally laid off at PT. Kaldu Sari Nabati Indonesia. This study uses research methods through a qualitative research approach by means of direct observation and then produces qualitative data presented in written form. The type of research in this study is empirical juridical research where this research originates from events that occur in the community regarding disputes over termination of employment. The results showed that the case of Termination of Employment (PHK) PT. Kaldu Sari Nabati Indonesia is a case of unilateral layoffs with the settlement of layoff disputes carried out through bipartite negotiations and mediation and will then proceed to the Industrial Relations Court stage if an agreement is not reached. Workers do not get compensation rights from the company. Companies must be given sanctions related to unilateral Termination of Employment (PHK) and compensation sanctions.